Nutritional benefits of ginger for patients with non-communicable diseases. (June 2022) - Baptista, Beatriz G.; Ribeiro, Marcia; Cardozo, Ludmila FMF; Leal, Viviane de O.; Regis, Bruna; Mafra, Denise
Summary: Ginger ( Zingiber officinale ) is a famous dietary spice rich in bioactive components like gingerols, and it has been used for a long time as food and medicine. Indeed, clinical studies have confirmed the anti-inflammatory and antioxidant properties of ginger. Thus, ginger seems to be an excellent complementary nutritional strategy for non-communicable diseases (NCD) such as obesity, diabetes, cardiovascular disease and chronic kidney disease. This narrative review aims to discuss the possible effects of ginger on the mitigation of common complications such as inflammation, oxidative stress, and gut dysbiosis in NCD.